Malay documents from Sulu and Mindanao in the British Library - Gallop, Annabel Teh (Journal of Philippine local history and heritage, 2016)
The British Library is an important repository for primary source materials on the Philippines in the 18th century, a period when the southern Philippine islands of Mindanao and the Sulu archipelago were of great interest to the English East India Company as potential sites for a trading base on the route to China. British involvement in the Philippines in this period culminated in the capture and brief occupation of Manila from 1762 to 1764, until its return to Spain at the end of the Seven Years War. The archival materials, largely held in the India Office Records in the British Library, are reasonably well-known and studied. But alongside the majority of papers in English and Spanish are a few documents in local languages such as Malay, Maguindanao, and Tausug, written in the modified form of the Arabic script known as Jawi. The contents of some of these documents are known from translations or parallel versions in English, and it is these versions which have been referenced in studies of this period. The original Jawi documents, however, have never been thoroughly examined. This paper focuses on the documents in Malay, with particular attention paid to use of language and formal diplomatic aspects such as annotations, calligraphy, and seals. Final remarks explore the richly multilingual landscape of Sulu and Mindanao, and the relative usage of Malay with respect to Tausug and Maguindanao, as well as foreign languages such as Arabic and Spanish.